Musicco : A Social Media Platform for Musicians - Steve Olsen, Maikol@Michael (Universiti Malaysia Sarawak (UNIMAS), 2019)
Entertainment industry is without a doubt, composed of a big part of the economy of a nation. Within our modern world where media such as movies, games, and music is considered dominant in our everyday lives, people often find ways to express themselves or even to get attention from others by using technologies. As of today, social media like Facebook and Twitter is almost within everybody’s reach. Due to the ease of accessibility as to the existence of mobile smartphones. To some, it may serve as chance for them to generate income. The huge amount of users of these mobile applications serves as a motivation for a whole lot of people in pursuing the latter idea. Not only that, it may serve as tool to promote oneself qualities and abilities, an assist to gain recognition and fame. Though, a generalized platform would be harder to manage as it will engender low focus onto the original targeted audience or costumers. Thus, a proposed system was designed to be a specific platform, particularly into music, to challenge the outcome that may come.